THE AVOIDANCE OF FEMALE CHARACTER TO FULFILL HER BASIC ROLES IN DANIELLE STEEL’S IRRESISTIBLE FORCES NOVEL - FIRMANI, FAHRIZAL N (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Avoidance, Basic Roles, Feminism, Motherhood Ideology, Career Woman, Irresistible Forces.For centuries, women are believed to have important roles in the family. It concerns with her primary task as a housewife and a mother. They are claimed to fulfill all of their husband’s need, do all household task; namely to clean and to cook, and accept their maternal instinct; such as nurturing and raising children. However, in this novel, we will find a different phenomenon. Danielle Steel in her Irresistible Forces describes a woman’s effort to gain her dream as a successfull career woman. In the process of achieving her success, she avoids her basic roles as a housewife and a mother.In conducting this research, the writer uses feminism approach to reveal the role of female character in her marriage life and her avoidance to fulfill her basic roles as a housewife and a mother. In analyzing this research, the writer chooses female major character in novel, Meredith Whitman, as the focus of the research.The research reveals that there are two avoidances of female character in Irresistible Forces novel concerning with her nature roles in the marriage. First, she leaves her basic roles as a housewife behind. Second, as a married woman, Meredith also refuses to fulfill her husband’s desire for having a baby by putting her motherhood off for fourteen years of their marriage.For the next researcher, if they are interested in exploring this novel, the writer would like to recommend to use different approaches such as psychological approach to observe how development of Meredith Whit man’s personality as a major female character.